Aspects of the diurnal cycle in a regional climate model - Peter Brockhaus; Daniel Lüthi; Christoph Schär (Meteorologische Zeitschrift, 2008)
We analyze the ability of the regional climate model CLM to simulate the European summer climate with particular consideration of mean diurnal cycles of precipitation, surface variables, convective indices and vertical temperature and humidity profiles. We consider three sets of simulations using different convective parametrizations (Tiedtke, Tiedtke-CAPE and Kain-Fritsch), each covering 6 summer seasons (April-September) driven by the ERA-40 reanalysis. Analysis shows that the afternoon peak of precipitation occurs 3-7 hours too early in the model. This may be linked to the underestimation of convective inhibition energy (CIN). We also observe an underestimation of the diurnal temperature range and a cold bias of about 1-3 K, resulting in a too shallow boundary layer. In addition, the boundary layer is found to be too well mixed and the night-time inversion to be strongly underestimated. Finally, the diurnal evolution of Iberian profiles is found to be influenced by the Iberian thermal low in both model and observations: Between 850 and 750 hPa, the temperatures are lower at noon than at midnight. As an explanation, we propose night-time subsidence heating in layers above 900 hPa.